Manual de funcionamiento, mantenimiento y aplicación pedagógica de equipos (batidora industrial) en el laboratorio de investigación de lácteos de la carrera de Agroindustria de la Universidad Técnica de Cotopaxi - Coyago Caiza, Dayana Gissel (2022)
This research aims to elaborate a manual of operation, maintenance, and pedagogical application of an industrial blender in the Dairy Research Laboratory of the Agroindustry Major. In the design and research modality, the descriptive method was applied, which allows detailing all the fundamental aspects of the operation, maintenance, and use of the industrial mixer, the generalities, technical specifications of the equipment, preventive maintenance, corrective maintenance, and personnel safety measures were determined; in addition, the inductive method was used, which is carried out through observation, registration, as well as a demonstrative practice that was conducted to verify the operation of the equipment; all of the aforementioned was done to contribute to increased motivation in students as well as improving the quality of education and thus successfully develop future research and projects; therefore, it provides students with concepts and theories necessary for their academic and technical training, thus helping to promote the use of pedagogical practices in the laboratories of the Agroindustry program.